Field Activited on Land Accumulation Property Right by Ethnic Buginese in Overseas - Ayuradi Miharja, Helmi; ., Saharuddin; Sjaf, Sofyan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTThis study aims to observe the most dominant arena which more influential effect on the accumulation of land ownership from the Bugis ethnic actors in the Village of East Mamburungan. Based on post positivist paradigm and theoritical field by Pierre Bouerdieu, perocessing by mixed method approach. The Object of this research, is Bugis ethnic actors who consist by 50 respondents. The results indicate that the economic field is the most dominant used by the actor than social field. The economic field by the actor also using as a patron-client system, land leases and the land transaction as a part of land accumulation process in order to support their social activities and establish their settlements (ethnic-based) in the Village of East Mamburungan.Keywords: field, ethnicity, actor, Buginese, land property rightABSTRAKRiset ini bertujuan untuk mengobservasi pilihan arena aktor yang lebih dominan berpengaruh terhadap akumulasi kepemilikan lahan oleh aktor etnik Bugis di Kelurahan Mamburungan Timur. Pendekatan riset ini menggunakan teori arena Bourdieu dengan paradigma penelitian yaitu post positivis, dimana data data kualitatif sebagai pendukung data kuantitatif, dimana aktor etnik Bugis yang dinilai sebanyak 50 responden. Hasil penelitian ini menunjukkan bahwa pilihan arena yang dominan berpengaruh yaitu arena ekonomi dibanding arena sosial terhadap akumulasi kepemilikan lahan. Arena ekonomi yang ditandai dengan sistem patron-klien, jual-beli lahan dan sewa lahan, sering digunakan untuk merebut pengaruh agar mempermudah aktor mengakumulasi kepemilikan lahan dalam mendukung aktivitas sosialnya dan membangun perkampungan berbasis etnik di Kelurahan Mamburungan Timur.Kata kunci: arena, etnisitas, aktor, Bugis, akumulasi kepemilikan lahan